Effective Prevention of Adolescent Substance Abuse – Educational versus Deterrent Approaches (Alberta Journal of Educational Research, 2012)
Substance abuse, especially among adolescents, has long been an important issue in society. In light of the adverse impact of substance abuse, scholars, educators, and policy-makers have proposed different approaches to prevent and reduce such abuse. This paper investigates the effectiveness of the two prominent approaches—educational and deterrent—in preventing and reducing adolescent substance abuse. The educational approach (e.g., school-based prevention programming) tends to be more comprehensive and better grounded in theories than the deterrent approach (e.g., drug testing). The educational approach not only targets multiple psychosocial factors contributing to substance abuse, but it is also supported by empirical studies showing that school-based prevention programming is effective in preventing substance abuse and has long-lasting positive influences on adolescent development. Practical implications of implementing school-based prevention programming are also discussed. L'abus d'alcool ou d'autres drogues, surtout chez les adolescents, constitue depuis longtemps une préoccupation importante de la société. À la lumière de l'impact défavorable de cet abus, les chercheurs, enseignants et décideurs ont proposé différentes approches pour le prévenir et le limiter. Cet article porte sur l'efficacité de deux approches importantes, l'une pédagogique, l'autre dissuasive, visant la prévention et la réduction de l'abus d'alcool ou d'autres drogues chez les adolescents. L'approche pédagogique (par ex. les programmes de prévention en milieu scolaire) est, de façon générale, plus globale et mieux fondée sur les théories que l'approche dissuasive (par ex. dépistage des drogues). Non seulement l'approche pédagogique cible-t-elle les divers facteurs psychosociaux qui contribuent à cet abus, elle est de plus appuyée par des études empiriques indiquant que les programmes de prévention en milieu scolaire sont des outils efficaces dans la prévention de l'abus d'alcool ou d'autres drogues et qu'ils ont un impact positif à long terme sur le développement des adolescents. Nous discutons des répercussions pratiques de la mise en œuvre des programmes de prévention en milieu scolaire.